Розвиток української мови у XVII-XVIII столітті - Горбовцова, І. В. (ХНУРЕ, 2019)
This paper highlights the variants of the origin of the Ukrainian language. The author makes an attempt to investigate the question of establishing the time of occurrence of Ukrainian language. To trance the main periods of its development.